GC–MS and HPLC Characterization of Amino and Fatty Acid Composition in Two Locally Produced Complementary Foods for Infants in Calabar, Nigeria - Oko, Gregory Elayeche; Onyinye Okonkwo, Chibuzor; Nnamdi Okonkwo, Sunday (JURNAL BIOSAINS, 2026)
Complementary foods are important foods for ensuring optimal nutrition and growth in infants and young children. They are expected to fill the nutritional gaps that arise when breast milk alone no longer meets the child's dietary needs However, the nutritional adequacy of homemade complementary foods, which are commonly used in many developing countries, is often deficient in important nutrients. This study evaluated the amino acid and fatty acid compositions of two indigenously formulated complementary foods designed for infants in Calabar, Nigeria. The formulations were produced using locally available ingredients: Blend A (rice, egg yolk, apple, and banana) and Blend B (rice, Titus fish, avocado pear, and banana). Amino acid and fatty acid profiles were analyzed using Gas Chromatography–Mass Spectrometry (GC–MS) and High-Performance Liquid Chromatography (HPLC) respectively. Results revealed that Blend A contained higher total fatty acids, dominated by oleic acid (89,700 ppm), linolenic acid (82,500 ppm), and linoleic acid (46,800 ppm), while Blend B exhibited more diverse amino acid composition, with phenylalanine (39.72 mg/100 g) and tryptophan (12.13 mg/100 g) as major essential amino acids. Both blends contained physiologically important fatty acids such as linoleic, α-linolenic, arachidonic, eicosapentaenoic (EPA), and docosahexaenoic (DHA) acids, crucial for infant development. The combined findings indicate that these locally formulated diets provide balanced macronutrient quality comparable to recommended dietary standards. The study establishes the potential of indigenous food resources as sustainable, cost-effective, and nutritionally adequate alternatives for complementary feeding and the prevention of childhood malnutrition in low-income settings.